Kadar Hormon Prolaktin Pada Kambing Peranakan Ettawa,Sapera dan Saanen Pada Berbagai Status Fisiologi - Sarmin Sarmin; Irkham Widiyono; Devita Anggraeni; Claude Mona Airin; Pudji Astuti (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2022)
This study examines the prolactin hormone profile in Etaawa, Sapera and Saanen lactating goats, adult females, pregnant does, and yearlings. This study used a total of 80 randomly selected goats with details of 26 Ettawa Crossbreed goats (eight lactating, six adult females, six pregnant, and six heifers), 32 Sapera goats (eight lactating, six adult females, twelve pregnant, and six yearlings) and 22 Saanen goats (five lactating, four adult females, six pregnant and yearling). All goats were declared clinically healthy. Blood sampling was performed through the jugular vein in each animal; then, serum was analyzed with an Enzyme-linked immunosorbent assay (ELISA) to prolactin concentration. High prolactin concentrations were found in Saanen goats in pregnant physiological status compared to Sapera and Ettawa crossbreed goats.